Airborne Transmission of the SARS-CoV-2 Delta Variant and the SARS-CoV-2 Omicron Variant - Byung Uk Lee (Aerosol and Air Quality Research)
Abstract An extensive study on the airborne transmission of respiratory viruses was published recently. The various kinds of discussions, including the history and scientific mechanisms behind viral aerosols were summarized in the study. However, the key experimental results were interpreted inadequately. The understanding in the study pointed toward an inappropriate direction for studies on viral aerosols in the COVID-19 pandemic. In this letter, two critical points from the point of view of aerosol sciences are discussed against the study on the airborne transmission of respiratory viruses. In the generation mechanism of viral aerosols, the important point is the viral load. The average viral loads in hosts infected with the SARS-CoV-2 Delta variant were unprecedentedly high, therefore the SARS-CoV-2 Delta variant aerosols must be considered in this pandemic. The viral load in respiratory fluids, rather than the preference of the virus toward small particles in deep respiratory tracts, was essential in viral aerosol generation. In addition, if the novel SARS-CoV-2 Omicron variant satisfies the fundamental conditions for universal principles of rapidly spreading respiratory viruses, the airborne transmission of the SARS-CoV-2 Omicron variant needs to be considered.